Antibiotics for the common cold—do they work?: …reducing waste in child health one intervention at a time. Issue 5 (18th September 2013) - Robinson, Joan
Abstract: Eco‐paediatrics is an occasional feature in Evidence‐Based Child Health: A Cochrane Review Journal. Our goal is to contribute to the worldwide discussion on reducing waste in health care. In each instalment, we will select a recent Cochrane review highlighting a practice, still in use, which the available evidence tells us should be discontinued.